Does Microfinance Empower Women from Economic, Social, and Political Perspectives ? : Empirical Evidence from Rural Gujarat - Patel, Ritesh; Patel, Nikunj (Prabandhan: Indian Journal of Management, 2021)
The objective of this study was to assess the impact of microfinance on rural women with respect to social, economic, and political empowerment. The study was carried out on 512 respondents belonging from Aravalli and Mehsana districts of North Gujarat. The districts and talukas were selected based on the highest and lowest rural women population. The villages were selected based on the highest rural women population. The study was conducted using the paired sample t-test. The study found that after joining the SHGs, the women were empowered significantly from the economic perspective ; they were somewhat empowered from the social perspective because on some of the criteria, the women were already empowered before joining the SHGs ; and the women were not empowered much on the political grounds after joining the SHGs. However, overall, the women were empowered after joining the SHGs.